2020
DOI: 10.3390/ma13183909
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Calculation of a Three-Dimensional Finite Element Model of Infiltration in Drainage Asphalt Pavement

Abstract: Drainage asphalt pavement provides excellent drainage performance and driving safety, where the permeability of the pavement is the critical performance. When analyzing the permeability of drainage asphalt pavements, the previously used two-dimensional infiltration calculation model with boundary conditions deviates from the real situation. In this article, a three-dimensional infiltration finite element method was proposed to evaluate the permeability of pavement, and the feasibility of the three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The current domestic technical specifications specify the temperatures corresponding to bitumen viscosity of 0.17 ± 0.02 Pa-s and 0.28 ± 0.03 Pa-s as the optimum mixing temperature and optimum compaction temperature of bitumen mixes, respectively [8]. Different RPRA high-viscosity bitumens were prepared by controlling the dosing of WTR at 2%, 3%, 4% and 5%, respectively.…”
Section: Study Of Wpe On Rpra's Viscosity-temperature Characteristicsmentioning
confidence: 99%
“…The current domestic technical specifications specify the temperatures corresponding to bitumen viscosity of 0.17 ± 0.02 Pa-s and 0.28 ± 0.03 Pa-s as the optimum mixing temperature and optimum compaction temperature of bitumen mixes, respectively [8]. Different RPRA high-viscosity bitumens were prepared by controlling the dosing of WTR at 2%, 3%, 4% and 5%, respectively.…”
Section: Study Of Wpe On Rpra's Viscosity-temperature Characteristicsmentioning
confidence: 99%
“…However, the increase in pavement length and rainfall intensity decreased the time required for the water to flow over the pavement surface. In another study, three-dimensional (3D) FE software (i.e., COMSOL Multiphasic) was employed to investigate the impact of the longitudinal slope on OGFC drainage capacity ( 11 ). To achieve this objective, a pavement with a width of 32 ft (10 m) and a length of 262 ft (80 m) was simulated using COMSOL.…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that the OGFC drainage capacity is strongly dependent on its porosity ( 8 , 9 ). In addition, pavement geometric design, including longitudinal and transverse slopes and pavement length, has been identified as a significant factor that affects OGFC hydraulic characteristics ( 10 , 11 ). Yet, previous studies have focused on the impacts of the OGFC layer itself and ignored the impacts of the underlying layers’ permeabilities on the drainage properties.…”
mentioning
confidence: 99%
“…Previously, researchers primarily used the homogeneous material concept to analyze the seepage features of asphalt mixtures [10,11]. However, the mesoscopic void structure of an asphalt mixture is complex, the void scale is extensive, and the spatial distribution is diverse.…”
Section: Introductionmentioning
confidence: 99%